Ebefrenie e schizofrenie: casi clinici e figure letterarie - Ferro, Filippo M. (B@belonline, 2021)
Life and story interact closely in building identity. In parallel, the case histories of psychopathology and the narratives of literature represent mirror images in describing reality and worldviews. Thus in German culture clinical figures such as the hebephrenia of Kahlbaum and Hecker, and therefore the schizophrenias of Bleuler and Binswanger, find precise consonances, and disturbing illuminations, if compared to the characters of Theodor Fontane and then to those eternalized by Thomas Mann and Franz Kafka.